(untitled) (Journal of Management and Educational Sciences, 2025)
The aim of this study is to investigate the effects of the CRSG exercise technique, which will be applied to people with chronic low back pain lasting at least six months, on pain, flexibility, balance, mobility and daily activities. The universe of the study consists of individuals with long-term low back pain problems between 2022-2023. The foam roller group (CRSG) and the home exercise group (EEG) are the two groups of the study. Individuals aged between 40 and 70 years, who had non-specific low back pain lasting more than 4 months, who were not included in an active exercise program, who did not have neurological deficits such as abnormal sensation, loss of muscle strength or loss of reflexes in the lower extremity and who did not have any indications for surgery were included in the study. The program in each group lasted eight weeks, three days a week and thirty minutes a day. The sessions in both groups consisted of three different parts: warm-up, main exercise and cool-down. The initial exercise part lasted forty minutes. The exercises in the program first consist of breathing and warm-up exercises. As a result of the study, it was found that there was no significant difference between the groups participating in the study in terms of pain, quality of life and physical functions (p>0.05). The foam roller group showed a significant difference in some parameters of the post-tests of both groups in terms of getting out of bed, driving, shopping, running, walking, general health status and pain intensity (p<0.05). There was a significant difference between the two groups in the parameters of CRSG in terms of walking long distances, pain intensity, general health status and feeling calmer and more peaceful (p<0.05). The results generally showed that foam roller exercises have a greater treatment effect than other types of exercises for people with low back pain (LBP).